Natural Variation of Epstein-Barr Virus Genes, Proteins, and Primary MicroRNA - Correia, Samantha (J Virol, 2017)
Viral gene sequences from an enlarged set of about 200 Epstein-Barr virus (EBV) strains, including many primary isolates, have been used to investigate variation in key viral genetic regions, particularly LMP1, Zp, gp350, EBNA1, and the BART microRNA (miRNA) cluster 2. Determination of type 1 and type 2 EBV in saliva samples from people from a wide range of geographic and ethnic backgrounds demonstrates a small percentage of healthy white Caucasian British people carrying predominantly type 2 EBV. Linkage of Zp and gp350 variants to type 2 EBV is likely to be due to their genes being adjacent to the EBNA3 locus, which is one of the major determinants of the type 1/type 2 distinction. A novel classification of EBNA1 DNA binding domains, named QCIGP, results from phylogeny analysis of their protein sequences but is not linked to the type 1/type 2 classification. The BART cluster 2 miRNA region is classified into three major variants through single-nucleotide polymorphisms (SNPs) in the primary miRNA outside the mature miRNA sequences. These SNPs can result in altered levels of expression of some miRNAs from the BART variant frequently present in Chinese and Indonesian nasopharyngeal carcinoma (NPC) samples. The EBV genetic variants identified here provide a basis for future, more directed analysis of association of specific EBV variations with EBV biology and EBV-associated diseases. IMPORTANCE Incidence of diseases associated with EBV varies greatly in different parts of the world. Thus, relationships between EBV genome sequence variation and health, disease, geography, and ethnicity of the host may be important for understanding the role of EBV in diseases and for development of an effective EBV vaccine. This paper provides the most comprehensive analysis so far of variation in specific EBV genes relevant to these diseases and proposed EBV vaccines. By focusing on variation in LMP1, Zp, gp350, EBNA1, and the BART miRNA cluster 2, new relationships with the known type 1/type 2 strains are demonstrated, and a novel classification of EBNA1 and the BART miRNAs is proposed.